Cellular Energy Absorbing TRIP-Steel/Mg-PSZ Composite: Honeycomb Structures Fabricated by a New Extrusion Powder Technology - Ulrich Martin; David Ehinger; Lutz Krüger; Stefan Martin; Thomas Mottitschka; Christian Weigelt; Christos G. Aneziris; Mathias Herrmann (Advances in Materials Science and Engineering)
Lightweight linear cellular composite materials on basis of austenite stainless TRIP- (TRansformation Induced Plasticity-) steel as matrix with reinforcements of MgO partially stabilized zirconia (Mg-PSZ) are described. Two-dimensional cellular materials for structural applications are conventionally produced by sheet expansion or corrugation processes. The presented composites are fabricated by a modified ceramic extrusion powder technology. Characterization of the microstructure in as-received and deformed conditions was carried out by optical and scanning electron microscopy. Magnetic balance measurements and electron backscatter diffraction (EBSD) were used to identify the deformation-induced martensite evolution in the cell wall material. The honeycomb composite samples exhibit an increased strain hardening up to a certain engineering compressive strain and an extraordinary high specific energy absorption per unit mass and unit volume, respectively. Based on improved property-to-weight ratio such linear cellular structures will be of interest as crash absorbers or stiffened core materials for aerospace, railway, or automotive applications.